IMPACT OF UNESCO ON STATES' CULTURAL POLICIES 2005 Convention on Diversity of Cultural Expressions - Couture Gagnon, Alexandre ([S.l.] : ROUTLEDGE, 2024)
The Impact of UNESCO on States' Cultural Policies focuses on the impact of the 2005 Convention on Diversity of Cultural Expressions on the cultural policies of eight states and substates, examining how they have integrated it into their own cultural policy. Cultural diversity presents a challenge for all governments. As migration increases and technology makes access to worldwide cultural products easier, governments seek to maintain a vibrant culture within their states or substates so that their populations can keep a strong sense of identity. Cultural policies become key to balance cultural diversity and national identity, or to promote them in parallel. The book addresses three main themes: how governments deal with cultural diversity, especially in their cultural policies; what the impact of an international convention on individual states' policies is; and how different states' status (i.e. size) on the international scene affects their implementation of an international convention. Providing a systematic comparative analysis, this book will be of great interest to students and scholars of public policy, cultural policy and international organizations. It will also be useful to policymakers involved in cultural policy.
Keywords: Cultural pluralism; POLITICAL SCIENCE / Public Policy / Cultural Policy; POLITICAL SCIENCE / Public Affairs & Administration